Improving fault prevention with proactive root cause analysis (PRORCA method) - Mohammadnazar, Hojat (2016)
Measures taken to prevent faults from slipping through to operation can secure development of highly reliable software systems. One such measure is analyzing the root causes of reoccurring faults and preventing them from ever appearing again. PRORCA method was developed in order to provide a proactive, lightweight and flexible way for fault prevention. To this end, PRORCA method relies on expert knowledge of the development context and development practices to identify individuals’ erratic behaviors that can contribute to faults slipping through to operation. The development of the method was done according to teachings of design science research. Three expert interviews with representatives of a case company supported the development of PRORCA. The first interview helped the problem identification and solution generation, while the other two interviews were carried out with the purpose of demonstrating the use of the PRORCA method in two different projects. Using the PRORCA proved to be easy and insightful findings were drawn from conducting it with respect to individuals’ erratic behavior in each project. Proactive analysis of faults using the PRORCA method supports development of highly reliable software systems in a simple, flexible and resource-friendly manner.